The Inverted Discoid Meniscus Segment: Clinical, Radiographic, and Arthroscopic Description of a Hidden Tear Pattern. (June 2016) - LaMont, Lauren; Ellis, Henry; Wise, Kelsey; Wilson, Philip
Background: A flipped, or inverted, meniscus segment is easily visualized in the normal meniscus. However, an inverted discoid meniscus segment may be difficult to appreciate because the tear occurs more centrally and leaves more meniscal rim; thus, it may be undertreated if not addressed during arthroscopy. Purpose: To describe findings on clinical history, radiographs, MRI, and arthroscopy of a lateral discoid meniscus with an inverted segment and compare them with characteristics of a lateral discoid meniscus without an inverted segment. Study Design: Case-control study; Level of evidence, 3. Methods: Between 2009 and 2012, a retrospective series of 121 consecutive knee arthroscopies for symptomatic lateral discoid meniscus were reviewed for the presence of an inverted fragment. Chart review of clinical presentation, operative reports, radiographic images, and arthroscopic images was performed. Comparative analysis of the clinical presentation between lateral discoid menisci with an inverted segment and noninverted lateral discoid menisci was performed by use of Fisher exact test and Mann-Whitney test. Results: Nineteen patients with an inverted discoid meniscus segment (14 males, 5 females; average age, 15.0 years; range, 9.5-17.0 years) were compared with 102 patients with a noninverted discoid meniscus (53 males, 49 females; average age, 12.3 years; range, 5-17.0 years) ( P = .011 for sex and P < .001 for age). All 19 discoid meniscus patients with an inverted segment had activity-related knee pain. Only 4 patients (21.0%) reported mechanical symptoms. Patients with an inverted discoid segment, compared with patients with discoid menisci without inverted segments, were more likely to have instability and effusion ( P = .012 and P < .001, respectively). Eighteen discoid meniscus patients with an inverted segment (94.7%) had an injury, while only 41.2% of patients with noninverted symptomatic discoid menisci had an injury ( P < .001). On MRI, an inverted discoid segment was seen as a horizontal longitudinal tear, a free fragment, or a double meniscus. During arthroscopy, the inverted discoid segment appeared normal, without a tear; upon probing, however, the inverted segment could be exposed. Conclusion: An inverted discoid segment occurs during adolescence, and it is more likely to occur in male patients and more likely to be associated with activity-related pain and injury compared with a noninverted symptomatic discoid meniscus. A discoid meniscus with an inverted segment does not have the standard radiographic and arthroscopic features normally associated with a discoid meniscus.